The Effect of Work Stress and Work Environment on Employee Loyalty Through Job Satisfaction Using the PLS-SEM Approach - Nia Nandini; Winarti; M Lukman Nurhakim; Althaaf Fawwaz Wanna (Psikoislamedia: Jurnal Psikologi, 2026)
Post-pandemic employee loyalty is crucial yet inconsistent, requiring job satisfaction as a mediator. To analyze loyalty determinants via work stress (pressure and role conflict) and work environment mediated by job satisfaction. A survey of 75 PT. XYZ employees was analyzed using PLS-SEM. The model explains 64.3% of loyalty variance (R2=0.643). Role conflict is the dominant predictor of job satisfaction (β=0.685), fully mediating its impact on loyalty (β=0.460). Physical work pressure is insignificant. The work environment has a significant direct effect on loyalty (β=0.268). Retention strategies are more effective through conflict management and a conducive environment rather than merely reducing workload.